Simultaneous determination of cordycepin and its metabolite 3′‐deoxyinosine in rat whole blood by ultra‐high‐performance liquid chromatography coupled with Q Exactive hybrid quadrupole orbitrap high‐resolution accurate mass spectrometry and its application to accurate pharmacokinetic studies. Issue 2 (21st November 2022) - Qi, Shenglan; Guan, Huida; Wang, Yongli; Fang, Qinqin; Cheng, Xuemei; Liu, Ping; Wei, Hai; Liu, Wei; Wang, Changhong
Abstract : Cordycepin from Cordyceps possesses excellent pharmacological properties, including anti‐inflammation and anti‐tumor effects, therefore representing a potential alternative medicine. However, doubts about the pharmacokinetic results of cordycepin had been raised in the previous study due to its rapid deamination. The organic solvent methanol was immediately added to terminate the degradation of cordycepin in anticoagulated blood samples and enable the accurate evaluation of pharmacokinetics in vivo. A sensitive and selective ultra‐high‐performance liquid chromatography coupled with Q Exactive hybrid quadrupole orbitrap high‐resolution accurate mass spectrometry method was developed and validated to simultaneously determine cordycepin and its deamination metabolite 3′‐deoxyinosine using 2‐chloroadenosine as an internal standard in rat whole blood. The calibration curves of cordycepin and 3′‐deoxyinosine showed excellent linearity within the concentration range of 1.05–10 000.00 ng/ml with acceptable accuracy, precision, selectivity, recovery, matrix effect, and stability. This method was successfully applied to the pharmacokinetic study of cordycepin and its metabolite in rat blood. The effect of the adenosine deaminase inhibitor erythro‐9‐(2‐hydroxy‐3‐nonyl) adenine hydrochloride on the pharmacokinetics of cordycepin was investigated. In summary, the reliable pharmacokinetic parameters of cordycepin and its deamination metabolite 3′‐deoxyinosine in rat blood were successfully elucidated. Erythro‐9‐(2‐hydroxy‐3‐nonyl) adenine hydrochloride considerably prolonged the half‐life of cordycepin in vivo.